1984
DOI: 10.1017/s0003356100027719
|View full text |Cite
|
Sign up to set email alerts
|

A note on the concentrations of plasma oestradiol-17β and progesterone around the time of puberty in heifers

Abstract: In heifers, plasma progesterone levels were low (<0-3 |xg/l) from the 59th to about the 15th day before puberty (defined as the day when oestrus was first detectable by the fern pattern of dried cervical mucus). Plasma oestradiol-17P levels varied randomly within the range 1 to 4 ng/1 over the same period, but then showed three peaks of about 6, 9 and 4 ng/1, respectively 8 days before puberty, on the day of puberty and 4 days later. The pre-pubertal oestradiol-17p peak was followed by a short period of elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
1
0
3
Order By: Relevance
“…The changes in plasma progesterone during the preand postpubertal periods were consistent with previous reports on puberty in ordinary cows (Gonzalez-Padilla et al, 1975;Suzuki and Sato, 1980;Glencross, 1984). Furthermore, formation of the corpus luteum and appearance of estrus behavior at puberty progressed in the same way as in ordinary heifers (Morrow, 1969;Suzuki and Sato, 1980;Moran et al, 1989).…”
Section: Discussionsupporting
confidence: 89%
“…The changes in plasma progesterone during the preand postpubertal periods were consistent with previous reports on puberty in ordinary cows (Gonzalez-Padilla et al, 1975;Suzuki and Sato, 1980;Glencross, 1984). Furthermore, formation of the corpus luteum and appearance of estrus behavior at puberty progressed in the same way as in ordinary heifers (Morrow, 1969;Suzuki and Sato, 1980;Moran et al, 1989).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, progesterone priming has been shown to enhance follicular estradiol-17β synthesis in ewes 59 and it has also been demonstrated that circulating estradiol-17β concentrations were higher at the first ovulatory estrus than in the preceding silent estrus. 60 Progestin administration hastens puberty by increasing LH secretion by accelerating the peripubertal decrease in estradiol-17β negative feedback effect. 61 As an example of the use of an exogenous progestin, melengestrol acetate (MGA) fed for 8 days followed by withdrawal enhanced onset of puberty by stimulating pulsatile LH secretion that accelerated follicle growth to the preovulatory stage.…”
Section: Use Of Progestins To Advance Pubertymentioning
confidence: 99%
“…Antes dessa fase, a concentração média de progesterona plasmática é extremamente baixa, entre 0,23 e 0,73 ng/ml (Balakrishnan et ai., 1986), dos dois a três meses antes da puberdade é de O, 12 ng/ml (Saxena e Gupta, 1992) e aos 35 dias O, 77 ng/ml (Peron e Fernandez, 1986). Numerosos autores (Gonzales-Padilha et ai., 1975;Bernardinelii et ai., 1979;Schams et ai., 1981;Schillo et ai., 1983;Me Leod et ai., 1984;Glencross, 1984;Balakrishnan et ai., 1986;Kinder et ai., 1987) descrevem uma ou mais elevações de progesterona plasmática antes do primeiro estro. Castenson et ai.…”
Section: Introductionunclassified